Analysis of Community Social Capital Inclusiveness Towards Waste Pollution Prevention by Shrimp Farming Company: A Case Study of Waste Pollution in Pasir Kuning Beach Area - Herdiyanti, Herdiyanti; Salfutra, Reko Dwi; Julia, Julia (Society, 2023)
Sewage pollution originating from the activities of shrimp farming companies in the Pasir Kuning Beach area raises serious concerns about its impact that damages the environment and disrupts the balance of the ecosystem. This research aims to understand and analyze the inclusiveness of social capital in local communities as an effort to prevent sewage pollution. Using a qualitative approach, this research conducted in-depth interviews with community members in the Pasir Kuning Beach Area. Respondents were selected based on criteria that ensured a balanced representation of various community groups, and secondary data was used to provide a broader context. The research findings highlight the central role of social capital in shaping relationships, trust, and cooperation among communities. The implications include developing more effective sewage pollution prevention strategies and providing a foundation for understanding community contributions to coastal ecosystem conservation. The focus on social capital inclusivity as a catalyst for positive change demonstrates the determination of local communities to overcome the negative impacts of shrimp farming activities. In the context of Bangka Belitung, which is affected by the mining sector, this research is significant in efforts to reduce environmental damage. It is hoped that these findings provide valuable insights for stakeholders in formulating sustainable solutions that support the ecology and well-being of local communities in the future.